STUDENT ACADEMIC ABILITY (STUDY ON STUDENT ACHIEVEMENT AT UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG) - Femi Handayani (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
The purpose of this study was to measure student, academic ability using cumulative grade point average achieved during the study at Universitas Islam Syekh-Yusuf Tangerang. By conducting in-depth interviews, observation, and direct involvement, comprehensive and detailed data was generated. The results showed that student, academic ability was not optimal although the cumulative grade point average was in the range of 3.0-3.27 which could be improved through the role of professional lecturers. A good learning process could help student, academic ability improvement.??Keywords: academic ability, the role of professional lecturers, a good learning process, grade point average